ONLINE IMPULSIVE BUYING IN THE DIGITAL ERA: INSIGHTS FROM PRICE, E-WOM, AND PURCHASE INTENTION UNDER ISLAMIC ECONOMICS PERSPECTIVE - Nisa, Choirun; Syarif, Ahmad; Rahmatullah, Nur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This research is motivated by the rapid development of the internet, which has significantly impacted daily life particularly in shifting consumer behavior toward online shopping. While online shopping offers convenience and attractive promotions, it also contributes to a rise in impulsive buying. From the perspective of Islamic economics, impulsive buying is viewed as a negative behavior, reflecting excessive consumption that contradicts the principles of wise and ethical wealth management. This study aims to examine the influence of price and electronic word of mouth (e-WOM) on impulsive buying, with purchase intention as an intervening variable, within the context of Islamic economic values. The research adopts a quantitative approach, collecting data from 100 undergraduate students at Sultan Aji Muhammad Idris State Islamic University Samarinda through questionnaires using simple random sampling. The findings reveal that both price and e-WOM have a significant effect on purchase intention in online shopping. Furthermore, price, e-WOM, and purchase intention each significantly influence impulsive buying. Additionally, purchase intention is found to mediate the relationship between price and impulsive buying, as well as between e-WOM and impulsive buying.